Study of the mental workload in the personnel of a television station - Domínguez Rivera, Dayana de la Caridad (2024)
In recent years, attention has been paid to emerging occupational diseases, especially to occupational hazards related to mental workload. The objective of this research is to evaluate the mental workload in workers of the Television Center of the municipality of Cárdenas, Cuba. A procedure consisting of 3 stages was followed, where in the first stage the sample to be studied was chosen by means of physical and psychological examinations, in the second stage the selected indicators were applied to each individual before and after the working day and in the third stage the results obtained were analyzed with statistical tools such as Excel and SPSS software. The results of the study indicated that in the sample there were significant differences between before and after the workday, mainly in the Director and Computer Science Specialist with considerable levels to be followed up, which evidences the existence of mental workload. The study showed the effects that the cognitive demands of the workplace can have on the health of workers and the need to apply preventive measures to reduce these negative effects.